2021
DOI: 10.3390/curroncol28010079
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mutations in a Lethal Case of Lymphomatous Adult T Cell Lymphoma with Cryptic Myocardial Involvement

Abstract: The autopsy of a 65-year-old diabetic African American male revealed significant left myocardial involvement by adult T-cell leukemia/lymphoma (ATLL) despite normal pre-mortem fluorodeoxyglucose (FDG) uptake by positron emission tomography/computed tomography (PET/CT). Due to pre-existing diabetic cardiomyopathy with reduced ejection fraction (EF) and compatible imaging studies, cardiac lymphomatous involvement was not suspected. While peripheral blood was negative for leukemia, next-generation sequencing of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Since these defects were demonstrated to be frequent in NB patients (van Engelen et al, 2009), Joucov and coworkers investigated this aspect and showed that depleting BARD1 (but also BRCA1) in frog embryos resulted in widely defective developmental phenotypes (including malformed neural tube and eye structures) (Joukov, Chen, Fox, Green, & Livingston, 2001), establishing a possible role of BARD1 in early organogenesis. In addition, very recently the BARD1 mutation R749K was reported in a fatal case of lymphomatous adult T-cell lymphoma with an ambiguous myocardial involvement (Hashemi Zonouz, Abdulbaki, Bandyopadhyay, & Nava, 2021).…”
Section: Bard1 Mutations In Cancer (And Other Diseases)mentioning
confidence: 99%
“…Since these defects were demonstrated to be frequent in NB patients (van Engelen et al, 2009), Joucov and coworkers investigated this aspect and showed that depleting BARD1 (but also BRCA1) in frog embryos resulted in widely defective developmental phenotypes (including malformed neural tube and eye structures) (Joukov, Chen, Fox, Green, & Livingston, 2001), establishing a possible role of BARD1 in early organogenesis. In addition, very recently the BARD1 mutation R749K was reported in a fatal case of lymphomatous adult T-cell lymphoma with an ambiguous myocardial involvement (Hashemi Zonouz, Abdulbaki, Bandyopadhyay, & Nava, 2021).…”
Section: Bard1 Mutations In Cancer (And Other Diseases)mentioning
confidence: 99%
“…A transcriptional analysis identified distinct transcriptomes between Japanese and North American cases [21], suggesting regional variations in ATLL pathophysiology. Several case reports identified novel mutations of ATLL [46,47]. Since clinical sequencing has been widely adapted, more novel mutations from other endemic areas will be identified through the analysis in future.…”
Section: Heterogeneity Of Genomic Alterations In Atll: Geographic Regmentioning
confidence: 99%